Dose-Dependent Anti-Inflammatory and Neuroprotective Effects of an ανβ3 Integrin-Binding Peptide. (14th November 2013) - Han, Shu; Zhang, Fan; Hu, Zhiying; Sun, Yayi; Yang, Jing; Davies, Henry; Yew, David T. W.; Fang, Marong
Abstract : Previous studies have shown that prevention of leukocyte infiltration by targeting integrins involved in transendothelial migration may suppress the clinical and pathological features of neuroinflammatory disease. This study was designed to investigate the effects of C16, an α ν β 3 integrin-binding peptide, in an acute experimental allergic encephalomyelitis (EAE) rat model. Multiple histological and immunohistochemical staining, electron microscopy observation, ELISA assay, Western blot, and magnetic resonance imaging (MRI) were employed to assess the degree of inflammation, axonal loss, neuronal apoptosis, white matter demyelination, and extent of gliosis in the brain and spinal cord of differently treated EAE models. The results showed that C16 treatment could inhibit extensive leukocyte and macrophage accumulation and infiltration and reduce cytokine tumor necrosis factor- α (TNF- α ) and interferon- γ (IFN- γ ) expression levels. A significantly lower clinical score at the peak time of disease was also demonstrated in the C16 treated group. Moreover, astrogliosis, demyelination, neuronal death, and axonal loss were all alleviated in C16 treated EAE animals, which may be attributed to the improvement of microenvironment. The data suggests that C16 peptide may act as a protective agent by attenuating inflammatory progression and thus affecting the expression of some proinflammatory cytokines during neuroinflammatory disease.